KORELASI KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA - Agus Syarifuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
Once children start school sitting bench, the role of parents can not be released. The attitude of parents complexion of the relationship between parents and children and how the attention of parents towards school, then all of this will affect the learning outcomes of children. According to Piaget that: "Children in the age range of 7-11 years old had only been able to think systematically about the objects and events that concrete.Based on the analysis, there was a significant influence between emotional intelligence and academic achievement of student mathematics SDN 2 Hilir Muara Kotabaru with a correlation coefficient r = 0.5786 and    rtabel = 1,734 at significant level 0.05, so that there is a correlation between Emotional Intelligence on the Result Learn math. Keyword: kecerdasan emosional, prestasi belajar